Phytosociological survey of spontaneous plants associated with soil conditions in the Paraíba swamp, Brazil - Costa, Paulo Marks de Araújo; Silva, Talita Stefany da (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
The analysis of phytosociology in sustainable agricultural systems is necessary because, in many cases, it is an indicator of soil problems and conditions, allowing the conduction and adequate management of the agro-ecosystem. Thus, the objective of the present study was to analyze the phytosociology of plants associated with soil conditions in an agroecological system in the region of the Paraíba swamp. The experimental analyzes were carried out in a total area of 342 m2. Soil sampling was carried out for the purpose of assessing chemical attributes. For the characterization of the species, the square inventory method with the dimensions 0.5 m × 0.5 m was used, which was launched four times at random throughout the area. The variables analyzed were: Relative density; absolute frequency; relative frequency; relative dominance; importance value index; relative importance. The results show that there was a relationship between the plants with the highest phytosociological expression and the soil conditions. The species with the greatest phytosociological representativeness were Cyperus rotundus and Amaranthus spinosus. The soil has high levels of organic matter, with low aeration and imbalance between nutrients.